A modified prognostic score for critically ill patients with cirrhosis: an observational study - Bao, Qiongling; Weng, Honglei (Journal of gastroenterology and hepatology, 2016)
Background and Aims: It is controversial whether patients with cirrhosis benefit from the intensive care unit (ICU) management. To identify the patients in whom ICU care may offer recovery, this study aimed to determine specific risk factors and to establish a novel prognostic score for 3-month mortality in critically ill patients with cirrhosis. Methods: An observational study was performed from August 2008 to May 2014, encompassing 349 critically ill patients with cirrhosis during their ICU stay (a 70% training and 30% validation set). Results: The overall 3-month mortality rate was 68.1% in training cohort. Prothrombin time, serum bilirubin, use of vasopressors, hepatic encephalopathy, and systemic inflammatory response syndrome at admission were identified as being strongly correlated with the 3-month prognosis. Based on these five variables, a modified score for critically ill cirrhosis (MSCIC) was developed. An increasing MSCIC was significantly correlated with a reduction in the rate of survival (P < 0.001). Moreover, excellent predictive power was found when the MSCIC was used (area under the receiver operating characteristic curve: 0.856 ± 0.047), which was significantly better than the prognostic efficiency of Acute Physiology and Chronic Health Evaluation II (P < 0.001), Model for End-stage Liver Disease (P = 0.02), Simplified Acute Physiology Score (P = 0.023), and the Child-Turcotte-Pugh score (P = 0.01); the MSCIC score was slightly better than that of Chronic Liver Failure-Sequential Organ Failure Assessment (P = 0.068). The similar result was obtained in validation set. Conclusions: The MSCIC is an easily adopted tool with a high prognostic efficacy for patients with advanced cirrhosis; MSCIC may act as a supplement to the clinical judgment of physicians when considering the prognosis.